Investigating the Relationship between Responsibility Perception and Pedagogical Aptitude - Kaur, Harjot (Journal of Research in Vocational Education, 2026)
Responsibility feeling is a teacher’s quality that holds great potential for advancing humanity. Regularity, sincerity, and fairness speak of the same language but in themselves, they are incomplete without the intervention of responsibility feeling. Likewise, teaching aptitude is a quality that in itself is incomplete without a sense of responsibility. In this connection, this study aims to explore how responsibility feelings influence teaching aptitude in Arunachal Pradesh. A sample of 137 secondary school teachers was evaluated using the Teaching Aptitude Test (TAT - GR) (1971) developed by Dr. S. C. Gakhar (Chandigarh) and Dr. Rajnish (Fazilka) and a Responsibility Feeling Test developed by the researcher according to the test construction and standardization procedure for measuring responsibility feelings of teachers, drawn from West Kameng district in Arunachal Pradesh by adopting a normative survey method of educational research. Statistical techniques such as Measures of Central Tendency, Measures of Variability, t - test, Percentile, and ANOVA were used. The findings reveal that teaching aptitude is average among the participants, with responsibility feelings playing a significant role. Statistical analysis using t - tests and ANOVA confirms the significant influence of responsibility feelings on teaching aptitude, emphasising the need for responsibility as a core quality in educators.